Réponse :
a) exp(3)×exp(2) = exp(3+2) = exp(5)
b) exp(15) = exp(5×3) = [exp(5)]³
c) exp(-5) =
d) exp(-10) =
Explications étape par étape
Copyright © 2025 ELIBRARY.TIPS - All rights reserved.
Lista de comentários
Réponse :
a) exp(3)×exp(2) = exp(3+2) = exp(5)
b) exp(15) = exp(5×3) = [exp(5)]³
c) exp(-5) =![\frac{1}{exp(5)} \frac{1}{exp(5)}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bexp%285%29%7D)
d) exp(-10) =![\frac{1}{exp(10) } =\frac{1}{exp(5\times 2) } = \frac{1}{[exp(5)]^{2} } \frac{1}{exp(10) } =\frac{1}{exp(5\times 2) } = \frac{1}{[exp(5)]^{2} }](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bexp%2810%29%20%7D%20%3D%5Cfrac%7B1%7D%7Bexp%285%5Ctimes%202%29%20%7D%20%3D%20%5Cfrac%7B1%7D%7B%5Bexp%285%29%5D%5E%7B2%7D%20%7D)
Explications étape par étape